Nilai Pendidikan dalam Novel IPA dan IPS Karya Putri Azzahra Haryanto - Cindy Pramadita; Irwansyah (Universitas Nias, 2023)
The study aims to describe (1) the educational value of Putri’s science and science novels azzhara haryanto, (2) the benefits of educational value in the science and social science novels by Putri Azzhara Hartanto. This study uses a literary sociological approach. This study uses a qualitative descriptive method. The data sources are IPA and IPS novels by Putri Azzhara Haryanto. The results of this study are (1) the results of this study are (1) the educational value of Putri Azzhara Haryanto’s scince and social sciences novels consists of physical education values, spritual education values, religious education values, moral education values, beauty education values (2) the educational value benefits of the science and social science novels by Putri Azzhara Haryanto consist of the educational values of skills, religion, decency, beauty and society.